THE ROLE OF THE CORPORATE SOCIAL RESPONSBIILITY IN THE HOTEL ATRIA MALANG - alan tri ihkwansyah (JIAGABI (Jurnal Ilmu Administrasi Niaga/Bisnis), 2018)
The purpose of this study was to analyze the Corporate Social Responsibility at Atria HotelMalang, and be able to find out the role of Corporate Social Responsibility that is most influential forinternal and stockolders at Atria Hotel Malang. This study uses a descriptive qualitative approach. Datacollection techniques use interview, observation and documentation techniquesThe results of the study found that Corporate Social Responsibility activities as a place to buildtrust and reciprocity from AMDAL and AMDALALIN that occurred due to the existence of a large companyin the area. Corporate Social Responsibility can also be a means of building relationships with residentsaround the company, customers, employees of the company, and stockholders. Corporate SocialResponsibility activities also have supporting factors and inhibiting factors, local residents and employeesand stockholders are the supporters of the Corporate Social Responsibility program. The obstacle toCorporate Social Responsibility is the adjustment of the Corporate Social Responsibility theme to theassistance desired by the community